High-resolution millimeter-wave spectroscopy of CH2DCl: Paving the way for future astronomical observations of chloromethane isotopologues. (June 2020) - Melosso, Mattia; Achilli, Andrè; Tamassia, Filippo; Canè, Elisabetta; Pietropolli Charmet, Andrea; Stoppa, Paolo; Dore, Luca
Highlights: Millimeter-wave spectra of CH2 DCl observed for the first time. Chlorine hyperfine structure resolved with Lamb-dip technique. Spectral predictions to guide radio-astronomical searches in the interstellar medium. Abstract: Chloromethane is the only organochloride detected in space to date. Its recent observation towards the low-mass protostar IRAS 16293-2422 with ALMA offers a prompt for new laboratory studies of CH3 Cl and its isotopologues. Here, we report the investigation of the rotational spectrum of monodeuterated chloromethane CH2 DCl in the frequency region between 90 and 300 GHz. The measurements have been carried out with a frequency-modulation millimeter-wave spectrometer, arranged to perform saturation spectroscopy. From the analysis of hyperfine-resolved spectra of the two chlorine isotopologues CH2 D 35 Cl and CH2 D 37 Cl, consistent sets of accurate spectroscopic parameters have been obtained. This work provides reliable spectral predictions which can be used to guide radio-astronomical searches of CH2 DCl in the interstellar medium and represents a solid base for future analyses of high-resolution infrared spectra of monodeuterated chloromethane.